DECALOGUE VIOLATION BY VASYL STEFANYK'S NOVELLAS CHARACTERS - Martinyuk , Ulyana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article analyzes some works of Vasyl Stefanyk through the prism of Christian morality (Ten Commandments of God); the discrepancy between the ideas of the characters who love God, live under his protection, and their actions, which contradict the Lord's instructions, is investigated; parallels are drawn between individual episodes from the biography of the master of the expressionist short story and tragic human destinies in the pages of his life sketches; on the example of quotations from Stefanyk's works, attention is focused on the problem of non-observance of the biblical Decalogue by the heroes of short stories; systematized works on the fall and misdeeds of Pokut peasants; the tragedy of people on the border is shown; outlines the causes of distortion of human consciousness that lead to sin. The article is based on a kind of parallel: biblical truths received by Moses on Mount Sinai – brought to despair, hopelessness, often suicide and crime, disadvantaged, hungry inhabitants of Pokut village, described by a true connoisseur of human psychology, singer of pain and truth Vasily Stefanyk. The material for the analysis was a collection-summary of the first period of V. Stefanyk's work – a book of selected works "My Word", which included short stories from previous collections: "Blue Book", "Stone Cross" and two new short stories "My Word" and "Court".